2020
DOI: 10.1073/pnas.2002613117
|View full text |Cite
|
Sign up to set email alerts
|

Functional plasticity and evolutionary adaptation of allosteric regulation

Abstract: Allostery is a fundamental regulatory mechanism of protein function. Despite notable advances, understanding the molecular determinants of allostery remains an elusive goal. Our current knowledge of allostery is principally shaped by a structure-centric view, which makes it difficult to understand the decentralized character of allostery. We present a function-centric approach using deep mutational scanning to elucidate the molecular basis and underlying functional landscape of allostery. We show that alloster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
124
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(140 citation statements)
references
References 52 publications
15
124
1
Order By: Relevance
“…These results bear some significance and support the latest illuminating study suggesting a model functional plasticity and evolutionary adaptation of allosteric regulation. 160 This function-centric model of allostery revealed remarkable functional plasticity of allosteric switches allowing modulate and restore regulatory activity through mutational combinations or ligand interactions. Our results similarly suggested that functional plasticity and cross-talk of allosteric control points in the SARS-CoV-2 RBD region can allow for differential modulation of recognition and long-range communication with ACE2 and antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…These results bear some significance and support the latest illuminating study suggesting a model functional plasticity and evolutionary adaptation of allosteric regulation. 160 This function-centric model of allostery revealed remarkable functional plasticity of allosteric switches allowing modulate and restore regulatory activity through mutational combinations or ligand interactions. Our results similarly suggested that functional plasticity and cross-talk of allosteric control points in the SARS-CoV-2 RBD region can allow for differential modulation of recognition and long-range communication with ACE2 and antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…The activity and substrate specificity of proteins can be manipulated via an array of high-throughput approaches with the endpoint being a mutation or a collection of mutations that meet the set criteria. Functional studies also show that multiple combinations of mutations (and just not one set) could rescue non-functional variants ( Leander et al., 2020 ) and context-dependence contributes to varied allosteric outcomes ( Tang and Fenton, 2017 ; Wang et al., 2020 ). But it is still not clear as to how the identified mutations affect the folding conformational landscape and hence, the interaction work or the distribution of conformational states to modulate activities.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these data point to a model in which mutations at evolutionarily conserved positions exert large (and often disruptive) effects on function while allostery is tuned at less conserved surface sites. For example, Leander et al recently used deep mutational scanning to map the pattern of compensatory mutations that rescued allosteric function for non-allosteric tetracycline repressor (TetR) variants ( Leander et al, 2020 ). In that study a ‘disrupt-and-restore’ strategy was used: an already-allosteric system was inactivated and deep mutational scanning was then used to identify compensatory mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In that study a ‘disrupt-and-restore’ strategy was used: an already-allosteric system was inactivated and deep mutational scanning was then used to identify compensatory mutations. While there are significant differences between rescuing a deficient variant and the optimization of a novel allosteric construct, they likewise found that the mutations at highly conserved sites were often disruptive to stability and function, while allostery-rescuing mutations occurred at weakly conserved and structurally distributed sites ( Leander et al, 2020 ). Similarly, mutations at ‘rheostat’ sites – weakly conserved positions distal to the site of regulation – were found to modulate allosteric control in human liver pyruvate kinase and the lactose repressor protein (lacI) ( Campitelli et al, 2020 ; Wu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%